Efforts to reduce illegal parking in Lampung Province - Sumbogo, Bambang; Oktaria, Eka Travilta; Barusman, M. Yusuf S.; Defrizal, Defrizal; Barusman, Andala Rama Putra (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: This study examines how land is designated as no-parking zones and the efforts to suppress illegal parking in Lampung Province. Research Methodology: The method used in this research is descriptive qualitative. Results: Findings show ten areas where parking is prohibited: on bends, shoulders, or bridges; pedestrian or bicycle tracks; near traffic lights; main roads; in front of or close to stopped vehicles; within 6 m of intersections; within 9 m of bus stops (unless damaged); within 3 m of fire hydrants or areas hindering fire-fighting access; along slippery roads; on overpasses, tunnels, or their approaches; and on grass verges or shoulders. To address illegal parking, the Lampung Province Transportation Agency has taken several measures: mapping parking zones, improving management to support traffic flow and local revenue (PAD), fostering community and government awareness, providing guidance to ensure proper management, and enforcing sanctions. However, emphasis is placed more on education and guidance than punishment. Conclusions: Effective parking management, supported by public awareness, government intervention, and structured regulations, is essential for traffic safety and efficiency. Limitations: The study is limited to Lampung Province and uses descriptive data, restricting broader generalization. Contribution: This research offers practical insights for regional governments to improve traffic order through structured parking management and emphasizes the role of education and community awareness in reducing illegal parking.